Aggregation-induced emission luminogens and tunable multicolor polymer networks modulated by dynamic covalent chemistry - Qin, Shilong; Zou, Hanxun; Hai, Yu; You, Lei (Chinese chemical letters, 2022)
Aggregation-induced emission (AIE) based luminescent materials are generating intensive interest due to their unique fluorescence in the aggregation state. Herein we report a strategy of dynamic covalent chemistry (DCC) controlled AIE luminogens for the regulation of multicolor emission in reversible covalent polymer networks. Tetraphenylethene derived ring-chain tautomers were prepared, and the emission was readily controlled through multimode, such as changing the solvent, adding the base, and dynamic covalent reactions with amines. Moreover, the construction of dynamic covalent cross-linked luminescent hydrogels with tunable fluorescent, self-healing, and mechanical properties, was realized. The combination of AIE and aggregation-caused quenching (ACQ) fluorophores in the polymer network further enabled the realization of a multicolor modulator, including white emission, in both solution and gel states. The strategies and results presented should find utility in dynamic assemblies, polymer networks, chemical sensing, and responsive materials. [Display omitted] .